A rare presentation of isolated right-sided pleural effusion in the context of ovarian hyperstimulation syndrome: A case report - Angela Vidal; Christiane Wachter; Alexandra Kohl Schwartz; Carolin Dhakal (Elsevier, 2021)
An isolated pleural effusion as the sole manifestation of early ovarian hyperstimulation syndrome (OHSS) is rare. A 38-year-old woman who had undergone in vitro fertilization presented with OHSS. Six days after transvaginal oocyte pickup, she presented with only an isolated right-sided pleural effusion and restricted respiratory capacity. A thoracentesis was successfull. Clinicians must be aware of unilateral pleural effusion, with a higher incidence on the right side, as a single-symptom presentation of OHSS. The case reported here illustrates the diversity and severity of OHSS.